Moisture and density (MAD) from IODP Hole 386-M0090A - Michael Strasser; Ken Ikehara; Jeremy D Everest; Lena Maeda; Katharina Hochmuth; Hannah Grant; Margaret S Stewart; Noriaki Sakurai; Takahiro Yokoyama; Rui Bao; Piero Bellanova; Morgane Brunet; et al. (PANGAEA, 2025)
Moisture and density (MAD) data from discrete samples from the above given hole of International Ocean Discovery Program (IODP) Expedition 386 (Japan Trench Paleoseismology). During the onshore phase of expedition 386, which took place between 2022-02-14 – 2022-03-15 onboard D/V Chikyu, discrete samples for MAD measurements (bulk density, dry density, grain density, water content, porosity, and void ratio) were taken from the work halves using 10 cubic centimetre syringes at an approx. down-core resolution of every 2 meters. Sampling depths were adapted and slightly modified for layers of special interest, such as tephras. Samples were processed and measured directly after sampling onboard Chikyu. For the measurements themselves samples were transferred to glass beakers of known weight and volume. For further methodological information see methods chapter in0.167emStrasser, M. et al., 2023 https://doi.org/10.14379/iodp.proc.386.102.2023